Metformin as a Therapeutic Option in Psoriasis: A Review of Pathophysiological Insights and Clinical Perspectives - Kozłowska, Kinga; Francuziak, Anna Ewelina; Dembicki, Piotr Mikołaj; Książek, Tomasz Karol; Szeliga, Aleksandra; Borowski, Maciej; Dzieszko, Natalia; Szczepański, Michał; Kalinowska, Weronika; Kulasza, Paulina Sara (Quality in Sport, 2025)
Aim of the study: This study synthesizes current preclinical and clinical evidence regarding the role of metformin as a potential therapeutic option in psoriasis, examining its mechanisms of action, efficacy, safety profile, impact on the common comorbidity of metabolic syndrome, as well as evaluating future directions for studies. Material and methods: A literature review was conducted using the databases PubMed, Scopus, and ScienceDirect up to April 2025 with keywords “metformin” AND “psoriasis”. Results: Preclinical studies demonstrate that metformin inhibits keratinocyte proliferation, promotes apoptosis, and suppresses key inflammatory mediators such as IL-23, IL-17, and TNF-α, mainly via AMPK activation and mTOR signaling inhibition. Clinically, adjunctive metformin therapy shows promising results in improving psoriasis severity indices, particularly in patients with coexisting metabolic syndrome, although study heterogeneity and dosing variability limit definitive conclusions. Moreover, metformin may improve metabolic parameters in psoriasis patients, potentially enhancing overall treatment outcomes. Safety data indicate a favorable profile with minimal adverse effects. Emerging research also suggests the potential application of metformin as a topical treatment. Conclusions: Metformin is a promising candidate to be implemented as part of the therapy targeting not only dermatological symptoms, but also comorbid metabolic disorders in psoriasis, which may contribute to more comprehensive and effective patient care. Despite encouraging findings, further randomized controlled trials are warranted to clarify optimal dosing, long-term efficacy, and mechanistic pathways.